Essay Review: The Star Gate Archives, Volumes 1-4: Reports of the US Government Sponsored Psi Program 1972-1995: 1 Remote Viewing 1972-1984, 2 Remote Viewing 1985-1995, 3 Psychokinesis, 4 Operational Remote Viewing Memorandums & Reports edited by Ed May & Sonali Marwaha - Broderick, Damien (Journal of Scientific Exploration, 2020)
For your consideration, two fragments of Twilit history (as Rod Serling might have put it), a dimension as time-stung as eternity, unnerving as a grating laugh at three in the dark chilly morning. One: In 1946, a would-be suicide named George B. J. Stewart attracted the interest of a beefy, bearded wingless angel named Santa Claus, and discovered how to shift into mirror universes. The post-Second World War US Congress quickly established a research center to contact other angels, especially those with working wings, and subsidized the program until 1974, when President Nixon’s resignation caused funding to dry up. Despite top-secret classification masking the CLARENCE program, Stewart is rumored to be alive and still active at the North Pole at the age of 111. Two: In 1972, three Scientologists and the brother in law of the third best chess grandmaster in history were invited by the US military to launch what would become a 19.933 million program devoted to psychic powers. The initial emphasis was operational, with trained clairvoyants casting their attention into far lands and even the future. Many branches of the intelligence community sought specific double- or triple-blind tasking, alarmed by rumors that the Soviets were making advances in this domain. Despite popular rumors, CIA were not heavily involved; the major funder was DIA (Defense Intelligence Agency). Along with NASA, DARPA, US Army Medical Research and Development Command, Foreign Technology Division and others, DIA repeatedly contracted this espionage methodology. Which, if either, of these ludicrous accounts is true? Well, it turns out that CLARENCE is merely a tall story (one I just concocted). By contrast, military research programs into psychic phenomena became public after long-hidden secret documents surfaced. Most recently, four immense volumes have been published by McFarland—dubbed collectively The Star Gate Archives—providing an opportunity to track government-funded scientific research into psi (purported mental abilities able to reach beyond limits established by canonical sciences). Despite those limits, for two decades the science edge of the program was situated on the West Coast at Stanford Research Institute (SRI) and then Science Applications International Corporation (SAIC). A 2017 summary paper states: “In July 1972, Russell Targ, as principal investigator, submitted a grant application on Research on Techniques to Enhance Extraordinary Human Perception to the Jet Propulsion Laboratory, NASA, with Dr. Harold Puthoff as co-investigator. This started the SRI program in psi research, which eventually closed in 1995 at SAIC.”[1] Its two most effective founding viewers were Ingo Swann and Pat Price, now deceased, both devotees of L. Ron Hubbard’s cult. For internal-security reasons, the success or failure of individual efforts were rarely revealed. But since the psi operatives were sometimes called back for further clandestine tasking, it seems evident that the results were often sufficiently effective and accurate in support of more conventional intelligence activities. There’s ample evidence for this in the various volumes. [1] https://www.academia.edu/38006378/THE_STAR_GATE_ARCHIVES_REPORTS_OF_THE_US_GOVERNMENT_SPONSORED_PSI_PROGRAM_1972-1995._AN_OVERVIEW